PENGEMBANGAN MEDIA COUNTING BOX UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG BILANGAN BULAT KELAS I SDIT SYIFAURRAHMAH - Syifaurrahmah; Nurdiana Siregar; Lailatun Nur Kamalia Siregar (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The research that has been carried out is entitled "Development of Media Counting Box to Improve the Ability to Count Integers of Grade 1 Students of SDIT Syifaurrahmah" which is based on the background that students' ability to count numbers in addition and subtraction materials is still lacking, as well as the lack of use of teaching aids from teachers so that students get bored easily so that their understanding of addition and subtraction materials has not been achieved. The research methodology uses research and development methods or often called Research and Development (R&D) using the ADDIE model. The data collection technique uses observation, interviews, questionnaires and documentation. Then the data analysis technique of this study uses qualitative descriptive analysis and quantitative descriptive analysis. The validity of the Counting Box learning media by media expert validators was 97%, by material expert validators was 98% with a very valid category. The results of practicality by the teacher's response were 94% and the students' response was 97% and the results of the analysis of the two respondents received an average score of 96% in the practical category. The students' learning outcomes were an average score of 82% obtained through pretest and posttest questions which showed that the Counting Box media was effective to use.